PERANAN EMPLOYESS STOCK OWNERSHIP PROGRAM, HUMAN COST EFFICIENCY DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSET - Yuliana, Haosana (Business Accounting Review, 2015)
In the company, shareholders expect managers to manage the company so as to maximize returns, while the manager is going to create strategy and goals to meet on their own needs than the needs of the owner (Pugh, Oswald, & Jahera, 2000). Then the Employee Stock Ownership Program (ESOP) is there to align employeeâs goals and objectives of the organization (Dhiman, 2009). With the ESOP, the employee is the owner of the company (Sanjaya, 2012), so as to encourage the increase of productivity, efficiency and has an impact to the firms overall profitability (Ngambi & Oloume, 2013). In this thesis, testing was done to the role of Employee Stock Ownership Program (ESOP), the Human Cost Efficiency (HCE) and Total Asset Turnover (ATO) towards Return on Asset (ROA) in the companys financial and investment sub-sectors. Based on the testing, ESOP, HCE and ATO had significant positive affect on ROA, in which if the companies implement ESOP and increasing the HCE and ATO, the ROA would also increase.